Etnoecologia, pesca e manejo comunitário de quelônios aquáticos na várzea do Baixo rio Amazonas - BARBOZA, Roberta Sá Leitão (Universidade Federal do Pará, 2014)
The aim of the present study was to describe, record and compare community management strategies for aquatic turtles in three communities of the Santarém floodplains, in the north of Brazil. Turtle consumption was also assessed in terms of preferences, rejections, food taboos and their use in popular medicine as a therapeutic resource. The turtle fishing techniques used were described, including seasonal and spatial variations, as were the species captured and the technique selection process, based on local knowledge. The income from fishing and the association between investment and return were assessed. The data were collected between June 2007 and July 2008. Informal conversations, monitoring of fishing activity and participant observation were carried out in the communities. Semistructured interviews, based on the dietary recall method (recall history), were also performed. These interviews recorded annual turtle consumption as well as memories of turtle fishing in the past. The first reports of turtle management in the Amazon region were made at the time of the first contact between Amerindians and Europeans. During the 1970’s, the Brazilian government implemented reforms based on centralized management controlled by the State. Currently, co-management exists in various locations of the Amazon region, such as the communities of Ilha de São Miguel, Costa do Aritapera and Água Preta. Although guided by community demand, the management of these three communities differs due to different levels of experience with management systems. On Ilha de São Miguel, turtle management has been present for almost 40 years, with a certain degree of success and vigor. Management techniques were established in Água Preta 22 years ago in a less rigorous manner. The recent implementation in Costa do Aritapera was not successful. In general, the inclusion of the main users of a natural resource in its management is difficult to execute. The great challenge for turtle management, as well as other wildlife resources in the Amazon region, is legal recognition of their use. Turtle consumption is a tradition rooted in Amazonian culture. However, it has been criminalized and as such, the majority of the population is constrained from doing so. As it is considered an illegal activity, there are no estimates of the quantity of animals exploited. This causes problems to those who want to implement sustainable methods of community management. Studies have shown that fish constitutes the main source of animal protein for the people of the Amazon region, whereas records of turtle consumption are relatively low. Differences were found in terms of the species of turtle consumed. In general, tracajá (Podocnemis unifilis) (meat and eggs) was the most commonly consumed species in the three communities, followed by pitiu (Podocnemis sextuberculata) (meat and eggs), which was mainly consumed in Costa do Aritapera. Turtles (Podocnemis expansa) are rarely consumed and there were no records of their eggs being collected. This meat is mainly consumed on Ilha de São Miguel. These differences could be associated with a combination of ecological factors and the management history of each community. No cultural differences were found between the communities in terms of the use of turtles. Podocnemis expansa, which is principally used in popular medicine, is the most rejected species whereas tracajá and pitiu are generally preferred. All three are considered to be “reimoso”. The most captured species was tracajá, followed by pitiu and tartaruga in lesser proportions. Tracajá can be found in different environments and collected at any time of the year in the three communities. Pitiu are mainly captured around Costa do Aritapera in periods of low water season. At this time, they are migrating from flooded forests areas in the direction of rivers and nesting beaches. Tartaruga are caught in the protected lakes of Ilha de São Miguel in times of flood. The fishing techniques employed vary depending on the level of the river. The fishermen recognize seasonal variations and, combined with local knowledge, use this information when selecting the technique to be used to catch turtles. Turtle fishing is usually carried out in a timely manner, during fishing expeditions. The yield of turtle fishing is greater when fish are not included and fishing by hand. Fishing by hand was more fruitful. Selective fishing aimed at capturing larger animals produced greater returns in terms of biomass. The yield based on CPUEN differed between the communities and the fishing periods in the present study, although there were no significant differences when biomass was calculated (CPUEB). The fishermen, in general, are not concerned with maximizing their income, because most fisheries are not for marketing. The yield reflects more the wisdom of a good fishing spot than the effort of displacement.When the patch was good fishermen spent little time while in less productive patches they spent more time. The present study suggests a number of ideas that could be adopted in order to facilitate the success of fauna community management. In the specific case of turtles, it is recommended that protected areas extend beyond the nesting areas and a quota system is introduced to take advantage of eggs that will be lost. There is a possibility of breeding commercialization.